The Comparison of Reproduction Biology of Capoeta trutta (Heckel, 1843) Populations from Ağın and Örencik Region of Keban Dam Lake - Özgür Canpolat; Metin Çalta (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to determine reproduction biology of Capoeta trutta (Heckel, 1843) obtained from Ağın and Örencik region of Keban Dam Lake. For this purpose, fish samples were monthly collected during a year and their sexes were determined. The maturation age for female Capoeta trutta caught from Ağın region was determined as 2 while it was 3 for females from Örencik regions. Maturation age was found to be 2 for male C. trutta for all regions. The Gonadosomatic Index Value (GSI) reached to the highest in May for both sexes and reproduction period for the fish was estimated between May and June.